Using Narrative Reflective Process to augment personal and aesthetic ways of knowing to support holistic person-centred relational practice. Issue 4 (3rd July 2020) - Schwind, Jasna K.; Manankil-Rankin, Louela
ABSTRACT: Oftentimes, when we, in the nursing profession, speak of knowledge development, we focus mostly on the empirical knowing. Although that is a significant component of how we know, we recognize the value of other ways of knowing, including personal, aesthetic, ethical, and emancipatory knowing. These patterns were originated by Carper in the late nineteen-seventies and more recently extended by Chinn and Kramer. As educators in nursing, we are concerned with how best to help students, future nurses, develop their personal and aesthetic knowing in order to more fully engage in relational practice with people in their care, thereby supporting holistic person-centred relational practice. To achieve our teaching-learning purposes, we implement Schwind's Narrative Reflective Process, which calls on creativity, metaphor, imagination, and reflective dialogue. In this article, we explicate how we use this creative approach in our work with students and offer the possibility of its benefit to other healthcare practitioners. Although we speak from the nursing perspective, we believe this creative reflective approach is transferable to other disciplines and contexts beyond nursing education, where holistic engagement in humane interaction is desired.